Anomalously High Heat Flow Regions Beneath the Transantarctic Mountains and Wilkes Subglacial Basin in East Antarctica Inferred From Curie Depth. Issue 1 (3rd January 2023) - Lowe, Maximilian; Mather, Ben; Green, Chris; Jordan, Tom A.; Ebbing, Jörg; Larter, Robert
Abstract: The Transantarctic Mountains (TAMs) separate the warmer lithosphere of the Cretaceous‐Tertiary West Antarctic rift system and the colder and older provinces of East Antarctica. Low velocity zones beneath the TAM imaged in recent seismological studies have been interpreted as warm low‐density mantle material, suggesting a strong contribution of thermal support to the uplift of the TAM. We present new Curie Point Depth (CPD) and geothermal heat flow (GHF) maps of the northern TAM and adjacent Wilkes Subglacial Basin (WSB) based exclusively on high resolution magnetic airborne measurements. We find shallow CPD and high GHF beneath the northern TAM, reinforcing the hypothesis of thermal support of the topography of the mountain range. Additionally, this study demonstrates, that limiting spectral analysis to areas with a high density of aeromagnetic measurements increases the resolution of CPD estimates revealing localized shallow CPD and associated high heat flow in the Central Basin of the WSB and the Rennick Graben (RG). Across the study area the CPD ranges from 15 to 35 km and the GHF values range from 30 to 110 mW/m 2 . The recovered CPD range is compatible with recent Moho depth estimates, as the CPD predominantly lies within the crust, rather than in the magnetite‐poor mantle. GHF estimates, based on the CPD estimates, show a good agreement to sparse in situ GHF measurements and the location of active volcanoes. Comparison to existing continent‐wide GHF estimates shows strong differences from magnetically‐derived heat flow estimates, while seismologically‐derived heat flow estimates show the best agreement to our results. Plain Language Summary: The Transantarctic Mountains (TAMs) separating the ancient East Antarctic region from the younger West Antarctic region. Recent studies found regions where acoustic waves move slowly beneath the TAM. Slow wave speeds are considered to be caused by warmer rocks at depth, which provide thermal support for the TAM. We present heat flow maps for this region. The estimated heat flow is based on "Curie Point Depths" (CPDs), which describes the depth at which magnetic rocks lose their magnetic properties due to increasing temperature. This temperature is called the Curie temperature (∼580°C for magnetite, the most common magnetic mineral in the Earth's crust). The heat flow at the surface is estimated from the depth at which this temperature is reached. We use for the first time for a CPD study in Antarctica exclusively high‐resolution magnetic data measured from aircraft. We demonstrated that limiting this method to airborne data improves the resolution of CPD variation, and thus heat flow estimates, substantially. We find shallow CPD and high heat flow beneath the TAM, which supports the suggestion that warmer rocks provide thermal support for the TAM. Additionally, we find high heat flow in the adjacent Wilkes Subglacial Basin and Rennick Graben. Key Points: Spectral analysis of exclusively aeromagnetic data over East Antarctica provides new Curie Point Depth and geothermal heat flow estimates High heat flow imaged beneath the Transantarctic Mountains reinforces the hypothesis that the topography is thermally supported Using exclusively airborne data improves the resolution of Curie depth estimation, revealing heat flow correlated to geological features